PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN E-LKPD PENCEMARAN AIR DALAM MENINGKATKAN LITERASI SAINS MURID SMP - Intan Permatasari; Elok Sudibyo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to determine the improvement in junior high school students' science literacy, the implementation of learning, and student responses after applying the guided inquiry learning model. The type of research used a pre-experimental design with a one-group pretest-posttest design. The subjects in this study were 25 students in class VII-D at Bahrul Ulum Junior High School in Surabaya. The science literacy indicators used were competency indicators in the aspects of explaining phenomena scientifically, compiling and evaluating designs for scientific investigation, interpreting data and evidence critically, and researching and using scientific information for decision-making and action. The results of this study indicate that there is a significant difference between the students' pretest and posttest scores after the guided inquiry learning model was implemented, with a t-test significance value of Sig. < 0.05. The N-Gain analysis results show an increase in junior high school students' science literacy of 0.59, which is categorized as moderate. Based on these data, it can be concluded that the application of the guided inquiry learning model is effective in improving junior high school students' science literacy on the subject of water pollution.